Social capital: The forgotten responsivity factor. (December 2020) - Koetzle, Deborah; Matthews, Betsy
The Risk-Need-Responsivity model of correctional intervention has become the cornerstone of correctional practice in the United States. With a primary focus on building human capital through interventions aimed at developing knowledge and skills needed for prosocial behavior, the model enjoys widespread empirical support. This approach, however, has been criticized by desistance-focused scholars for its failure to recognize social capital and the importance of social networks for facilitating behavior change. The current article examines the concept of individual-level social capital and describes how its development can be integrated into the Risk-Need-Responsivity model of correctional interventions as an important responsivity factor. Recommendations include assessing for social capital and strategies for enhancing both bonding and bridging social capital.